2005
DOI: 10.1590/s0004-27492005000100005
|View full text |Cite
|
Sign up to set email alerts
|

Estudo laboratorial das micoses oculares e fatores associados às ceratites

Abstract: Laboratory analysis showed predominance of filamentous fungi over the yeasts, and keratitis was the main observed ocular infection. Fungal keratitis involved at least one associated factor in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 12 publications
3
12
0
2
Order By: Relevance
“…Ocular surgical procedures prior to ocular infection were significantly more associated with infection by yeasts. Topical antibiotics were used both in both yeast and filamentous fungal infections (27) . The large number of corneal buttons we examined came from patients with fungal infection who had undergone surgery, therefore these patients had used antibiotics and anti-inflammatory agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocular surgical procedures prior to ocular infection were significantly more associated with infection by yeasts. Topical antibiotics were used both in both yeast and filamentous fungal infections (27) . The large number of corneal buttons we examined came from patients with fungal infection who had undergone surgery, therefore these patients had used antibiotics and anti-inflammatory agents.…”
Section: Discussionmentioning
confidence: 99%
“…If this is not done, a sample can be collected from the ulcer, due to the significant probability of discovering the diagnosis even after the onset of treatment. As test results take a long time, and taking into account the urgency of the situation, in vivo confocal microscopy can be used to guide treatment earlier (25)(26)(27)(28)(29)(30)(31)(32)(33) .…”
Section: Discussionmentioning
confidence: 99%
“…Com nexo causal já bem estabelecido, o trauma vegetal é citado em diversos estudos como um importante dado na história clínica de lesões corneanas suspeitas de infecções fúngicas (2,16,17) . A baixa incidência de infecções por leveduras pode ser a razão do baixo índice de fatores predisponentes encontrados no estudo (4,7) . Por outro lado, a alta incidência de fungos filamentares encontrados coincide com estudos que mostram este sendo mais comuns em pacientes hígidos e sem doença ocular prévia (18)(19)(20) .…”
Section: Discussionunclassified
“…O aumento na incidência de casos deve-se, provavelmente, ao uso irrestrito de antibióticos de amplo espectro, que propiciam um ambiente de baixa competitividade, favorecendo o crescimento do fungo (2) . Outros fatores a serem considerados são o uso abusivo de cor ticoides tópicos, olho seco, lentes de contato, cirurgias oculares prévias, uso de medicações ou doenças imunossupressoras e doenças que alterem a flora ocular (3)(4)(5)(6)(7) . Embora com características clínicas particulares, as infecções fún gicas geralmente confundem-se com as bacterianas, tornando a pesquisa etiológica laboratorial mandatória.…”
unclassified
“…Filamentous fungi are responsible for the majority of these cases (4) . Höfling-Lima et al (5) cited filamentous fungi as responsible for 79% of fungal keratitis and showed that the genus Fusarium is responsible for 59% of the fungal keratitis in patients of the Federal University of São Paulo.…”
Section: Introductionmentioning
confidence: 99%